2020
DOI: 10.1037/spq0000407
|View full text |Cite
|
Sign up to set email alerts
|

How the history of American Psychological Association Division 16 can shape the future of school psychology: Demonstrating organizational transformation.

Abstract: Over the past 75 years, the history of Division 16 (School Psychology) has been integral to the science and practice of school psychology. As a constituent body of the American Psychological Association (APA), the division has advocated for role definitions and professional boundaries within APA and has represented the specialty of school psychology within the larger community of psychology. Since the convening of school psychology’s Thayer Conference in 1955, the division has remained steadfastly committed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…to proactively anticipate the dynamics of a classroom, be sensitive to early warning signs of psychological difficulties, respond when challenges occur, and maintain attitudes devoted to improving the educational milieu for all students. To alter the status quo, D16 governance, bodies overseeing training standards, and journal editors must embrace the changing dynamics (Doll et al, 2020; Gilman et al, 2020; Henington et al, 2020; Reynolds, 2020). We strongly recommend that school psychology professionals commit to the social justice action in the School Psychology Unified Antiracism Statement and Call to Action (Garcia-Vazquez et al, 2020) to eradicate racism and educational disparities; ensure that culturally adapted, evidence-based comprehensive services are equitability accessible to all students with needs (Hughes et al, 2020; Nastasi et al, 2020); and rejuvenate programs of research to consider the ecology, physiology, psychology, and culture of each student (Jimersen et al, 2020; Klingball et al, 2020; Kranzler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to proactively anticipate the dynamics of a classroom, be sensitive to early warning signs of psychological difficulties, respond when challenges occur, and maintain attitudes devoted to improving the educational milieu for all students. To alter the status quo, D16 governance, bodies overseeing training standards, and journal editors must embrace the changing dynamics (Doll et al, 2020; Gilman et al, 2020; Henington et al, 2020; Reynolds, 2020). We strongly recommend that school psychology professionals commit to the social justice action in the School Psychology Unified Antiracism Statement and Call to Action (Garcia-Vazquez et al, 2020) to eradicate racism and educational disparities; ensure that culturally adapted, evidence-based comprehensive services are equitability accessible to all students with needs (Hughes et al, 2020; Nastasi et al, 2020); and rejuvenate programs of research to consider the ecology, physiology, psychology, and culture of each student (Jimersen et al, 2020; Klingball et al, 2020; Kranzler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They proposed achieving this target by enhancing training, creating coalitions (instead of simply partnerships) with other school psychology organizations, promoting culture and diversity in school psychology, and closing the gap between the need for and the availability of school psychologists. Doll et al’s (2020) recommendation epitomize the perspective of Conoley et al (2020), who noted that transformation can and should occur at an organizational level, starting with graduate training, continuing through research, gaining momentum through organizational leadership, and then clearly being demonstrated in practice.…”
Section: Understanding and Integrating The Past Present And Futurementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the APA DSP has taken seriously the call to represent both doctoral and nondoctoral school psychologists, and although this regularly put them at odds with many APA doctoral specialties, the DSP leadership never wavered in their commitment to represent all school psychologists (Doll et al, 2020). In a dramatic and somewhat surprising move, the APA has decided that, after more than 125 years, the entry level within professional psychology may need to be adjusted to recognize masters level practitioners.…”
Section: What's So Special About the School Psychology Specialty?mentioning
confidence: 99%